DAMPAK PENDISTRUBUSIAN ZAKAT PRODUKTIF BAITUL MAL ACEH TERHADAP SOSIAL EKONOMI MASYARAKAT - Saifuddin; Hasbi (Lembaga Riset dan Inovasi Kreyat Center, 2023)
The distribution of productive zakat has an important role in inclusive economic development in Aceh. Zakat is not only a social charity but also an instrument to improve the economic welfare of society at large. This article outlines several positive impacts of the productive use of zakat, including economic empowerment of the community, development of small and medium enterprises, increased financial access, and development of social infrastructure. The discussion also covered the importance of effective and transparent zakat fund management to ensure optimal impact. Thus, the distribution of productive zakat in Aceh is not only aimed at reducing poverty but also at encouraging inclusive and sustainable economic growth.